On Nano áº›Ù€preÙ€gÙ€Open Set - Esmaeel, Rana B.; Jassam, Ahmed. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
In this work, the notion is defined by using and some properties of this set are studied also, and Ù€ set are two concepts that are defined by using ; many examples have been cited to indicate that the reverse of the propositions and remarks is not achieved. In addition, new application example of nano was studied.